2020
DOI: 10.1101/2020.04.16.20068221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning to predict 5-year survival among pediatric Acute Myeloid Leukemia patients and development of OSPAM-C online survival prediction tool

Abstract: Background: Acute myeloid leukemia (AML) accounts for a fifth of childhood leukemia. Although survival rates for AML have greatly improved over the past few decades, they vary depending on demographic and AML type factors. Objectives: To predict the five-year survival among pediatric AML patients using machine learning algorithms and deploy the best performing algorithm as an online survival prediction tool. Materials and methods: Pediatric patients (0 to 14 years) with a microscopically confirmed AML were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…The lack of reproducibility in research on artificial intelligence in general ( 44 ) is also likely to be a future issue in biomedical use-cases of SSL as unfortunately only a minority of studies provide publicly accessible code to support their results ( 11 , 19 , 27 , 28 , 30 , 38 , 40 ). As is evident from previous studies on SSL in oncology, use cases mainly include tumor entities with high prevalence such as breast ( 15 17 , 25 28 , 33 35 , 37 , 41 ), lung ( 18 , 22 , 23 , 33 , 34 , 38 , 41 ), and colorectal cancer ( 11 , 12 , 34 , 35 ) where single centers can amass sufficiently sized data sets to conduct SSL experiments. This is also reflected in the overwhelming absence of studies on SSL in hematology with only one single study ( 40 ) including any hematological neoplasm at all.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of reproducibility in research on artificial intelligence in general ( 44 ) is also likely to be a future issue in biomedical use-cases of SSL as unfortunately only a minority of studies provide publicly accessible code to support their results ( 11 , 19 , 27 , 28 , 30 , 38 , 40 ). As is evident from previous studies on SSL in oncology, use cases mainly include tumor entities with high prevalence such as breast ( 15 17 , 25 28 , 33 35 , 37 , 41 ), lung ( 18 , 22 , 23 , 33 , 34 , 38 , 41 ), and colorectal cancer ( 11 , 12 , 34 , 35 ) where single centers can amass sufficiently sized data sets to conduct SSL experiments. This is also reflected in the overwhelming absence of studies on SSL in hematology with only one single study ( 40 ) including any hematological neoplasm at all.…”
Section: Discussionmentioning
confidence: 99%
“…To grade breast cancer samples, Das et al. ( 17 ) employ a Generative Adversarial Network (GAN) where the discriminator uses an unsupervised model that is stacked over a supervised model with shared parameters to utilize both labeled and unlabeled samples. An Auxiliary Classifier GAN that divides lung cancer samples into malignant and benign patches which allows for subsequent pixel-based PD-L1 scoring is reported by Kapil et al.…”
Section: Studies On Semi-supervised Learning In Cancer Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, ML can predict breast cancer survivability in the primary stages. 34 - 36 Das et al 37 and Hauser et al 38 have compared selected ML methods to the survival prognosis of patients with leukemia. They have respectively found that the gradient boosting algorithms (BAs) such hist gradient boosting (HGB) with area under the curve (AUC) of 0.779 and XGBoost with AUC of 0.87 achieve the highest performance.…”
Section: Introductionmentioning
confidence: 99%